A Dual-Pointer guided transition system for end-to-end structured sentiment analysis with global graph reasoning. Issue 4 (July 2022) - Xu, Qiujing; Li, Bobo; Li, Fei; Fu, Guohong; Ji, Donghong
Abstract: Structured sentiment analysis is a newly proposed task, which aims to summarize the overall sentiment and opinion status on given texts, i.e., the opinion expression, the sentiment polarity of the opinion, the holder of the opinion, and the target the opinion towards. In this work, we investigate a transition-based model for end-to-end structured sentiment analysis task. We design a transition architecture which supports the recognition of all the possible opinion quadruples in one shot. Based on the transition backbone, we then propose a Dual-Pointer module for more accurate term boundary detection. Besides, we further introduce a global graph reasoning mechanism, which helps to learn the global-level interactions between the overlapped quadruples. The high-order features are navigated into the transition system to enhance the final predictions. Extensive experimental results on five benchmarks demonstrate both the prominent efficacy and efficiency of our system. Our model outperforms all baselines in terms of all metrics, especially achieving a 10.5% point gain over the current best-performing system only detecting the holder-target-opinion triplets. Further analyses reveal that our framework is also effective in solving the overlapping structure and long-range dependency issues. Highlights: We design a transition-based system for end-to-end structured sentiment analysis. We propose a novel Dual-Pointer module into our model to better term recognition. We introduce a global graph reasoning mechanism for effective high-order features. We advance the state-of-the-art performance of structured sentiment analysis.